2010
DOI: 10.1016/j.oftal.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Estudio comparativo entre cirugía de catarata por microincisión coaxial y facoemulsificación estándar

Abstract: CCMIC is an effective and safe technique that offers an excellent alternative for cataract surgery, with a smaller incision and postoperative outcomes comparable to the standard technique. Prospective studies with more patients and longer follow-ups are needed to establish if there really are statistically significant and clinically relevant differences between both techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…Our findings support the results of a recent comparative study of coaxial microincision cataract surgery and standard phacoemulsification (Capella & Barraquer 2010). In this study, an endothelial cell loss of 7.7% was observed in the conventional phacoemulsification group and of 4.98% in the coaxial mircoincision group at 3 months after surgery.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings support the results of a recent comparative study of coaxial microincision cataract surgery and standard phacoemulsification (Capella & Barraquer 2010). In this study, an endothelial cell loss of 7.7% was observed in the conventional phacoemulsification group and of 4.98% in the coaxial mircoincision group at 3 months after surgery.…”
Section: Discussionsupporting
confidence: 92%
“…One trial was conducted in Bosnia and Herzegovina (Musanovic 2012), 13 trials in China (Hui 2016; Li 2016; Lin 2013; Luo 2012; Mao 2008; Shan 2016; Shi 2013; Wang 2009; Yao 2008; Yao 2011; Yu 2016; Zhang 2014; Zhu 2014), one trial in France (Febbraro 2015), one trial in India (Vasavada 2013a), one trial in Italy (Mastropasqua 2011), five trials in Korea (Hwang 2008; Hwang 2016; Jeong 2013; Li 2011; Moon 2011), two trials in Spain (Capella 2010; Morcillo-Laiz 2009), one trial in Switzerland (Dosso 2008), and one trial in Turkey (Can 2010). …”
Section: Resultsmentioning
confidence: 99%
“…When the study investigators reported the method of randomization, we judged the study to be at low risk of selection bias. We judged Capella 2010 to be at high risk of bias because it was reported as a “prospective and randomised study” (p269), but the authors noted through email correspondence that the treatment assignment was by “alternating one-by-one.”…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations